ICT procurement : pre-award ambiguities in requirement analysis and post-award ICT projects effects in government sector - Vaheed, Mohamed Maharoof (2021)
The Information Communication and Technology (ICT) industry offers major revolution in propelling the economy of a country, but statistics and literatures on ICT project implementations have been reported to be underperforming especially with regards to untimely delivery, exceeding budgets, and the lack of quality of the systems delivered, that causes major concerns and frustrating. In addressing these concerns, this thesis has performed a research study on the ICT procurement process chain that deemed to affect the performance of ICT projects in government agencies by referencing among others, the 2013 Malaysian Ministry of Finance, ICT procurement guideline. It analyzes the 3 phases of the ICT procurement chain specifically the pre-tender, post-tender and post-award phases and the corresponding resolve while adopting three theories namely the dialectical theory, resource-based theory, bureaucratic theory, and some combination of these theories were explored. These theoretical perspectives appear to establish in that they help to describe different resolutions that can arise within the ICT procurement lifecycle and collectively understand the reasons why and when ICT projects fail, so that the process can be improved. To begin with, a pilot study was conducted with a 33 questions reliability survey that resulted a Cronbach Alpha of 0.766 from 30 non-random respondents. Subsequently in the main study, respondents from three groups from the public agencies namely the business functional users, ICT technical teams, ICT procurement teams and the fourth group being the ICT vendors were surveyed quantitatively to form a sample size of 338 responses. The respondents were mainly from the levels of divisional heads and similar representing the public agencies and from the vendors were the ICT consultants and senior project leaders. A statistical analysis with SPSS analytical software was produced in order to comprehend the process of ICT procurement and the challenges it encounters within the process chain. This result was used to develop set of questions for the purpose of validating the study by a qualitative method. In the development of qualitative questions, a panel of 5 senior experienced experts from both the public organizations and ICT vendors were asked to review and comment on the clarity and the construction of the interview questions. This qualitative method is designed as a case study was tested on 5 senior management members from the public agencies and ICT vendors in order to review policies, standards, and practices that are used currently to procure ICT systems, and to determine how and why some projects were unsuccessful. The outcome found that at the pre-tender and post-tender phases, firstly, there are absence of skilled resources, which includes insufficient knowledge, and inexperience personnel at the level of functional users and ICT team. Secondly, technical requirements are ambiguous due to lack of expertise at the agencies ICT team to produce the exact requirements and thirdly, the dialectics between these different units contribute to other post-award implementation issues. Eventually this study had resulted in a development of an improved ICT procurement process that were assented by the experts. The study’s novelty is its research of horizontal-based procurement processes and gaps, in addition of its analysis on issue-by-issue process phase’s themes and concerns.